Biotransformação de diterpeno clerodano e do ibuprofeno por fungos endofíticos e modificação química de compostos orgânicos - Vasconcelos, Daniely Holanda Pinto (2018)
This thesis presents the results of four independent studies described in four chapters. The first chapter describes the biotransformation of the diterpene 3,12-dioxo-15,16-epoxy-4-hydroxycleraloda-13 (16), 14-diene by the cell cultures of the endophytic fungi Lasiodiplodia gonubienses, Neofusicocumum ribis and Pseudofusicoccum stromaticum of the Botryosphaeriaceae family. P1, P2, P3 and P6 are the bioproducts obtained in these study, the last three are unpublished in the literature. In addition, two semi-synthetic derivatives were obtained from P2, one acylated and the other alkylated, both inedited in the literature. The second chapter describes the biotransformation of ibuprofen by the fungus Neofusicoccumum ribis, obtaining the hydroxylated product (IB-1), as well as five semi-synthetic derivatives (IB-M, IB-Et, IB-But, IB- BrCN and IB -ClP). The third chapter relates to synthetic preparation of medicine precursors fluoxetine (Pr-FLX1 and Pr-FLX2) and three derivatives (FLX-Be, FLX-PCl, R-FLXH), the compounds Pr-FLX2, FLX-PCl and R-FLXH are inedited in the literature. The fourth and last chapter describes the achievement of four semisynthetic derivatives (D2, D3, D4 and D9) are obtained from the natural product 4-(4'-O-acetyl-α-L-raminosyloxy)benzylisothiocyanate through Nuleophilic addition reactions.